Manuel Castells’ theory of information society as media theory - Kirtiklis, Kęstas (Lingua Posnaniensis, 2017)
The present article deals with one of the most elaborated theories of information society, proposed by Manuel Castells. Castells defines the present social landscape as the Information Age, in which human societies perform their activities in a new technological paradigm and argues that this landscape was brought about by the revolution of information and communication technologies (ICT) at the second half of the 20th century. I argue that Castells first and foremost theorizes these new ICT (in the vein of media theorist Marshall Mc-Luhan) and discerns their three main features – network logic, timeless time and space of flows which are visible only in the interaction of media and society. Therefore, Castells’ ICT / media theory serves as a kind of methodological framework for his theory of the information society.